THE OPTIMAL CAPITAL STRUCTURE: AN EMPIRICAL STUDY OF INDONESIA COMPANY IN THE FOOD AND BEVERAGE INDUSTRY - Sylviana Maya Damayanti; Jane Julia Mulyono; Isrochmani Murtaqi (Ekonomi dan Bisnis, 2017)
Optimal capital structure is mix between debt and equity which resulted in maximizing firm’s value. Food and beverage sub-sector industry play an important role in Indonesia economic growth as one of the biggest contributor of gross domestic product (GDP) in Non-Oil & Gas Industry. The aim of this study is to determine the optimal capital structure in Indonesia food and beverage manufacturing. Data used in this study from 14 food and beverage companies listed in Indonesia Exchange. This study used Adjusted Present Value (AVP) simulation by Aswath Damodaran to determine the optimal capital structure. This simulation started with estimated the unlevered company value then as the level of debt increase the unlevered company value adjusted by the net effect of both the benefit of debt and cost of debt. Company value estimated at each level of debt from 10% - 90% and the debt ratio which resulted in highest company value is the optimum debt ratio. The result from this study shows that there are two companies should have the 0% debt ratio.